Apuntes sobre los actos jurídicos personalísimos: una categoría necesaria - Moia, Ángel Luis (Universidad Nacional del Litoral, 2020)
The legislative incorporation of personal rights and the consequent category of extra-patrimonial legal relations require a rethinking of the generaltheory of institutes as the legal act. The current regulations are analyzed by projecting them on the precepts of the legal act, addressing twospecific emergencies such as the autonomy of the will and representation.